1980
DOI: 10.1083/jcb.86.3.810
|View full text |Cite
|
Sign up to set email alerts
|

Apparent coordination of the biosynthesis of lipids in cultured cells: its relationship to the regulation of the membrane sterol:phospholipid ratio and cell cycling.

Abstract: The coordination of the syntheses of the several cellular lipid classes with one another and with cell cycle control were investigated in proliferating L6 myoblasts and fibroblasts . Cells cultured in lipid-depleted medium containing one of two inhibitors of hydroxymethylglutaryl-CoA reductase, 25-hydroxycholesterol or compactin, display a rapid, dose-dependent inhibition of cholesterol synthesis. Inhibition of the syntheses of each of the other lipid classes is first apparent after the rate of sterol synthes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

1980
1980
2002
2002

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(9 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…Consistent with this hypothesis are the recent reports linking membrane phospholipid synthesis, in particular that of PC, to DNA synthesis (Hirata and Axelrod, 1980) and passage through the cell cycle (Cornell and Horwitz, 1980). These studies (Cornell and Honvitz, 1980;Hirata and Axelrod, 1980) emphasize that changes in phospholipid synthesis can lead to alterations in membrane composition and fluidity which may be important in triggering cell growth.…”
Section: Pcmentioning
confidence: 99%
“…Consistent with this hypothesis are the recent reports linking membrane phospholipid synthesis, in particular that of PC, to DNA synthesis (Hirata and Axelrod, 1980) and passage through the cell cycle (Cornell and Horwitz, 1980). These studies (Cornell and Honvitz, 1980;Hirata and Axelrod, 1980) emphasize that changes in phospholipid synthesis can lead to alterations in membrane composition and fluidity which may be important in triggering cell growth.…”
Section: Pcmentioning
confidence: 99%
“…6, Fig. 1) (Holley et al, 1974;Cornell et al, 1977; Cornell and Horwitz, 1980). Bettger et al showed that a lipid supplement improved the clonal growth of human diploid fibroblasts in a defined medium (Bettger et al, 1981).…”
Section: Discussionmentioning
confidence: 99%
“…L6 myoblasts cultured in medipm containing delipidized serum and biotin were arrested in G1 when an inhibitor of hydroxymethylglutaryl-CoA reductase, 25-hydroxycholestero1, was added to the medium (Cornell and Honvitz, 1980). Lipid synthesis occurred after the removal of 25-hydroxycholesterol and the cells then synthesized DNA and multiplied (Cornell and Horwitz, 1980). Phosphatidylinositol synthesis was increased in serum starved cells after serum or growth factor stimulation (Ristow et al, 1980).…”
mentioning
confidence: 99%
“…To measure the protein synthesis rate by myoblasts in the presence of cycloheximide, [''H]leucine (2 pCi/ml) was added simultaneously with 10 kg/ml cycloheximide. At 10, 30, 45, 70, and 100 min thereafter, the radioactivity incorporated into TCA-precipitable material was determined by adding 5% TCA directly to the culture plates as described in the accompanying paper (5) . The rate of glycoprotein synthesis of 52-h myoblast cultures was estimated by adding ['"C]fucose (0 .5 yCi/ml) after 50 h in culture and measuring the radioactivity incorporated into cold 5% TCA-precipitable material at 52 h .…”
Section: Synthesis Ratesmentioning
confidence: 99%